New legal approaches to studying the Court of Justice revisiting law in context (Collected Courses of the Academy of European Law, 2020)
the beginning of 2015, the Court of Justice opened its archives, which created a new and challenging primary source for those studying the Court of Justice: the dossiers de procédure which contain much more than the contemporary documents published by the Court. This volume includes five chapters which analyse the activities of the Court of Justice from a highly diverse range of non-doctrinal perspectives. However, they also highlight significant new developments at the Court itself which attract attention and deserve analysis. Thus, the idea behind this volume is to make available new tools and approaches through which the activities of the Court of Justice can be studied. It shows a more intense engagement with scholars across disciplines to reflect on law and courts, with the Court of Justice as a central focus, and new methods (such as network citation analysis) and sources (such as the Court's archives) being discovered and developed. It also shows a more intense and deeply knowledgeable engagement with EU law and the Court of Justice by non-legal scholars, such as the new sociologies and histories of the Court of Justice. These and other new approaches have spawned productive and ongoing conversations across disciplines. --